(untitled) (Ameghiniana, 2013)
The Devonian distribution of trilobites in Austral South America is analysed. Some ecological boundaries applied to these trilobites are determinated and, based in these reasons and in generic distribution, two Faunal Provinces for trilobites are defined: 1) an Eastem Province (Atlantic) that is equivalent to the "Malvinokaffric Province" of Richter and Richter, and 2) a new Province in Pacific (Andean) position for which the name "Austral Andean Province" is proposed.